2018
DOI: 10.1051/0004-6361/201834006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a massive dust-trapping vortex connected to spirals

Abstract: Context. Spiral arms, rings and large scale asymmetries are structures observed in high resolution observations of protoplanetary disks, and it appears that some of the disks showing spiral arms in scattered light also show asymmetries in millimeter-sized dust. HD 135344B is one such disk. Planets are invoked as the origin of these structures, but no planet has been observed so far and upper limits are becoming more stringent with time. Aims. We want to investigate the nature of the asymmetric structure in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 84 publications
9
106
1
Order By: Relevance
“…There are many observational examples of discs containing vortices that could potentially be the result of planet disc interactions (e.g. van der Marel et al 2013;Isella et al 2013;Fukagawa et al 2013;Pérez et al 2014;Marino et al 2015;Kraus et al 2017;Dong et al 2018;Cazzoletti et al 2018). These are also particularly interesting cases to us as, similarly to the HL Tau and TW Hydrae cases, allow us to make tentative predictions about the planets in these systems.…”
Section: Oph Irs 48mentioning
confidence: 99%
See 2 more Smart Citations
“…There are many observational examples of discs containing vortices that could potentially be the result of planet disc interactions (e.g. van der Marel et al 2013;Isella et al 2013;Fukagawa et al 2013;Pérez et al 2014;Marino et al 2015;Kraus et al 2017;Dong et al 2018;Cazzoletti et al 2018). These are also particularly interesting cases to us as, similarly to the HL Tau and TW Hydrae cases, allow us to make tentative predictions about the planets in these systems.…”
Section: Oph Irs 48mentioning
confidence: 99%
“…The disc surrounding the Herbig Ae/Be star HD135344B (Pérez et al 2014;Cazzoletti et al 2018) shows interesting phenomena. This disc contains a cavity with a radius of ≈ 50AU at the edge of which is a bright ring of material.…”
Section: Hd135344bmentioning
confidence: 99%
See 1 more Smart Citation
“…The most striking result of these observations is the ubiquity of annular structures, colloquially described as gaps and rings. While some discs do show alternative structures like spirals or crescents (e.g., van der Marel et al 2013;Casassus et al 2015;Pérez et al 2016;Boehler et al 2018;Cazzoletti et al 2018), most of the discs observed at high resolution are characterised by axisymmetric structures. The prevalence of axisymmetric structures was already clear from the publication of several high-resolution observations targeting individual sources (ALMA Partnership et al 2015;Isella et al 2016;Andrews et al 2016;van der Plas et al 2017;Fedele et al 2017;Loomis et al 2017;Fedele et al E-mail: cas213@cam.ac.uk 2018; Dipierro et al 2018;Clarke et al 2018) and from the survey in Taurus (Long et al 2018), but recently it was made even clearer by the publication of DSHARP (Andrews et al 2018b;Huang et al 2018), a homogeneous high resolution survey of 20 discs.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting results obtained using ALMA and VLT is the detection of substructures on images of protoplanetary disks observed with high angular resolution (see, e.g. Avenhaus et al, 2018;Cazzoletti et al, 2018;van Boekel et al, 2017). Statistical analysis shows that the observed substructures often have ring-like form, less often they look like wrapped spiral arms and very rarely exhibit crescent-like azimuthal asymmetries.…”
Section: Introductionmentioning
confidence: 99%